1990
DOI: 10.2214/ajr.155.5.2120934
|View full text |Cite
|
Sign up to set email alerts
|

Osteochondral impaction of the femoral head associated with hip dislocation: CT study in 35 patients.

Abstract: Chondral

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 3 publications
1
19
1
Order By: Relevance
“…This study saw a 40% incidence, with an impaction in the obturator type of dislocation. The region of impaction is in direct contradiction to what was seen by Tehranzadeh et al (3). Their study revealed posterolateral impactions, whereas the defects in our study were in the anterior and superolateral margin of the head.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This study saw a 40% incidence, with an impaction in the obturator type of dislocation. The region of impaction is in direct contradiction to what was seen by Tehranzadeh et al (3). Their study revealed posterolateral impactions, whereas the defects in our study were in the anterior and superolateral margin of the head.…”
Section: Discussioncontrasting
confidence: 99%
“…The frequency ofosteochondral impaction fractures ranges from 12% to 100% (3,4). This study saw a 40% incidence, with an impaction in the obturator type of dislocation.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…With the introduction of 3-D imaging it is possible not only to accurately diagnose the lesion but also stage it, which has a direct bearing on the surgical procedure to be employed. Early detection of avascular rotational osteotomy or core decompression with or without vascularized grafting initiated in the initial period lead to preservation of joint function [11]. In the present study 5 cases of avascular necrosis of the femoral head underwent 3-D CT imaging which clearly delineated areas of sclerosis, compression and contour alteration of head of femur along with acetabular involvement (Fig 7).…”
Section: Discussionmentioning
confidence: 50%
“…Using arthroscopy in 29 patients as a standard of reference, Khanna et al [82] showed that acute traumatic injury to the hip resulted in loose bodies (59%), intraarticular step deformities (38%), osteochondral lesions (49%), and labral tears (93%). Traumatic hip dislocation was shown to be frequently (20/32, 63%) associated with osteochondral impaction fractures [83], which typically result in posttraumatic osteoarthritis.…”
Section: Traumatic Cartilage Injuriesmentioning
confidence: 99%